2008
DOI: 10.1158/0008-5472.can-08-0035
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Melanoma Cell Death Using Inhibitors of Protein Disulfide Isomerases to Abrogate Survival Responses to Endoplasmic Reticulum Stress

Abstract: Exploiting vulnerabilities in the intracellular signaling pathways of tumor cells is a key strategy for the development of new drugs. The activation of cellular stress responses mediated by the endoplasmic reticulum (ER) allows cancer cells to survive outside their normal environment. Many proteins that protect cells against ER stress are active as protein disulfide isomerases (PDI) and the aim of this study was to test the hypothesis that apoptosis in response to ER stress can be increased by inhibiting PDI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
158
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(167 citation statements)
references
References 43 publications
(58 reference statements)
5
158
0
4
Order By: Relevance
“…45 In cutaneous metastatic melanoma, we have recently demonstrated the clinical potential of ER stress-induced apoptosis, with BRAF wt melanomas showing greater sensitivity, compared with tumours harbouring hyperactivating mutations in the BRAF protein kinase. 32,33 Moreover, we have also shown (and confirmed in the present study) that BRAF mutation is associated with increased levels of basal autophagy. 20 Interestingly, ER stress-induced apoptosis is reduced in melanoma cells harbouring oncogenic BRAF compared with the observed induction in BRAF wt melanoma cells, and in this context and in contrast to observations in BRAF mutant melanoma cells, we have also shown that autophagy inhibition significantly sensitizes BRAF wt melanoma cells to ER stressmediated apoptosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…45 In cutaneous metastatic melanoma, we have recently demonstrated the clinical potential of ER stress-induced apoptosis, with BRAF wt melanomas showing greater sensitivity, compared with tumours harbouring hyperactivating mutations in the BRAF protein kinase. 32,33 Moreover, we have also shown (and confirmed in the present study) that BRAF mutation is associated with increased levels of basal autophagy. 20 Interestingly, ER stress-induced apoptosis is reduced in melanoma cells harbouring oncogenic BRAF compared with the observed induction in BRAF wt melanoma cells, and in this context and in contrast to observations in BRAF mutant melanoma cells, we have also shown that autophagy inhibition significantly sensitizes BRAF wt melanoma cells to ER stressmediated apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously shown that BRAF-mutated melanoma cells display reduced sensitivity to ER stress activation compared with wt cells, suggesting that an abrogated ER stress response may limit drug-induced apoptosis in these cells 20,32 (Figure 1). We therefore hypothesised that the reduced ER stress response observed in BRAF mutant melanoma cells results from chronic ER stress that desensitizes them to further stress stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,[35][36][37] In this study, we show that ERp29 is a novel regulator in modulating cell growth arrest and phenotypic changes associated with MET in proliferative/invasive breast cancer cells. Importantly, we show that ERp29 is a potential tumor suppressor in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of identifying PDI isoform(s) responsible for CDDP resistance, we transfected pools of siRNAs to selectively and individually inhibit the expression of various PDI isoforms. Four isoforms have been selected because of their previously characterized role in survival to ER stress (PDIA1), 30 in Ca 2 þ exchange (PDIA3) 31 and their overexpression in the present study (PDIA4 and PDIA6). Thus, siRNAs against these four isoforms allowed efficient knockdown in A549-resistant clones with limited off-target effects in 48 h (Supplementary Figure S3).…”
Section: Wt R2mentioning
confidence: 99%